Changes in the inflammatory markers with supplementation of channa striatus extract in post lower segment caesarean section - Shafii, Noorazliyana
Objecti1•e: Channa striatus or Haruan was found to have beneficial effect for wound healing and anti-inflammatory due to its' amino acids and fatty acids content. The objective of this study was to determine the effect of C.striatu .~ supplementation on inflammatory markers which are high sensitive C-reactive protein (hsCRP), total white cell counts (TWCC) and platelet counts in post Lower Segment Caesarean Section (LSCS) patients. De.sig11: This was a randomized; double blinded, placebo-controlled sntdy among post LSCS women conducted in Hospital Universiti Sains Malaysia from March 2010 to December 2012. Material and Methods: A Total of 33 patients from C.striatus and 27 patients from placebo group were included in this study. Participants in the treatment group consumed 500 mg of freeze dried Cstriatu.~ extract daily while the participants in placebo group consumed 500 mg of placebo daily for 3 days. Venous bloods for hsCRP, TWCC and platelet counts were taken from each participant postoperatively at day I and day 3. Results: Within C. striatus group, there were significant reduction in hsCRP (P < 0.001) and TWCC (P < 0.001), with significant increase in platelet count (P < 0.001) from day I to day 3. Similar pattern of changes were observed within control gro up. Between group comparison at day 3 post operatively indicates no significant difference in hsCRP (P = 0.275), TWCC (P = 0.983) and platelet count (P = 0.206) benveen the nvo groups. Conclusion: In conclusion, there is no significant difference in the inflammatory markers during wound healing in post LSCS women.